SERUM PROTEIN PROFILE OF MALARIA PATIENTS THROUGH SDS PAGE METHOD - Shams, Saira; Ahmed, Shabir; Ayaz, Sultan; Abd_Allah, E. F.; Shams, Sumaira; Niaz, Sadaf; Gul, Irum; Gul, Naila; Ullah, Riaz (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Malaria is a crucial disease that causes huge mortality and morbidity, along with economic losses in term of purchasingmedicines in underdeveloped countries such as Pakistan.Materials and Methods: A total of 150 human blood samples were collected from the Districts of Karak and Kohat KhyberPakhtunkhwa, in Pakistan, and were examined through microscopy and then all positive samples were analyzed by SDS-PAGE methodfor the detection of antibodies against plasmodium.Result: The overall prevalence of malaria was found to be 18% (27/150). The prevalence of plasmodium species was “21.3% (16/75) and14.6% (11/75) in the Districts of Karak and Kohat respectively. The prevalence of plasmodium species i.e. P. vivax and P. falciparum, inthe Districts of Karak and Kohat, was found to be 14.6% (22/150) and 3.33% (5/150) respectively. Among these, P. vivax 10.6% (8/75)and P.falciparum 4% (3/75) were noted in the District of Kohat; while P. vivax 18.6% (14/75) and P. falciparum 2.6% (2/75) were foundin the District of Karak Khyber Pakhtunkhwa, Pakistan respectively”. The serum protein of malaria patients were 57KDA and 78KDAbands, which were determined by Sodium Dodecyl Sulfate Poly-Acrylamide Gel Electrophoresis (SDS-PAGE) technique.Conclusion: The SDS page method is the most accurate diagnostic assay and was recognized as a most reliable method in the diagnosisof antibodies produced against Plasmodium spps. The proteins bands of Serum protein of malaria patients may be undertaken for study todevelop possible future vaccine.